The Effect of the Parametric Decay Instability on the Morphology of Coronal Type III Radio Bursts - Sishtla CP; Jebaraj IC; Pomoell J; Magyar N; Pulupa M; Kilpua E; Bale SD (IOP Publishing Ltd, 2025)
The nonlinear evolution of Alfven waves in the solar corona leads to the generation of Alfvenic turbulence. This description of the Alfven waves involves parametric instabilities where the parent wave decays into slow mode waves giving rise to density fluctuations. These density fluctuations, in turn, play a crucial role in the modulation of the dynamic spectrum of type III radio bursts, which are observed at the fundamental of local plasma frequency and are sensitive to the local density. During observations of such radio bursts, fine structures are detected across different temporal ranges. In this study, we examine density fluctuations generated through the parametric decay instability (PDI) of Alfven waves as a mechanism to generate striations in the dynamic spectrum of type III radio bursts using magnetohydrodynamic simulations of the solar corona. An Alfven wave is injected into the quiet solar wind by perturbing the transverse magnetic field and velocity components, which subsequently undergo the PDI instability. The type III burst is modeled as a fast-moving radiation source that samples the background solar wind as it propagates to emit radio waves. We find the simulated dynamic spectrum to contain striations directly affected by the multiscale density fluctuations in the wind.